Soil Properties and the Abundace of Ironwood (Eusideroxylon zwageri Teijsm.& Binn.) Varieties in Jambi, Indonesia - Bambang Irawan (Institut Pertanian Bogor (IPB University), 2015)
Two series of a study on the correlation between soil properties and distribution of ironwood (Eusideroxylon zwageri Teijsm.& Binn.) varieties had been conducted in Senami, a natural forest stand, Jambi, Indonesia. The first was using purposive random sampling. The samples were taken from the locations where the E. zwageri varieties naturally grow in the depth of 0–30 cm and 30–60 cm. The number of composite samples was 18 which were analyzed for chemical soil properties. The second study was conducted using systematic sampling where 64 soil cores were collected from 3 different soil depths namely 0–20 cm, 20–40 cm, and 40–60 cm. The physical soil properties were analyzed from the 64 soil samples. The research results revealed that the drainage among E. zwageri varieties varied from poor conditions to moderate, while the bulk density was slightly different, from very low to low. The results also show that E. zwageri varieties are able to grow in almost any soil textures. There is no specific correlation between chemical soil properties and distribution of E. zwageri varieties. All varieties grow at almost the same condition of chemical soil properties except var. grandis.